'A book in his hand, – but it couldn't be a prayer-book': The Self-Awareness of William Harrison Ainsworth's Newgate Novels. (3rd July 2018) - Ibitson, David A
Abstract: This article argues that William Harrison Ainsworth's Newgate novels Jack Sheppard (1839–40) and Rookwood (1834) exhibit a self-awareness of both their contextual literary culture, and of the critical opposition that defines the Newgate genre of the 1830s and 40s. Jack Sheppard, alongside Charles Dickens's Oliver Twist, is shown to both depict and exploit contemporary concerns about the harmful influence of popular literature which were exacerbated by the Courvoisier case of 1840. Its portrayal and use of a society saturated by dangerous literature ironically contradicts Ainsworth's own protestations of innocence at his text's implication in Courvoisier's murder of Lord William Russell. This article establishes that pre-existing eighteenth-century and Romantic anxieties about literature consumption are a precursor to Newgate's exploration of such issues at the start of the Victorian period. Ainsworth's novels are shown to be concerned with standards of literature, the unreliable interpretation and ungovernable appropriation of both literature and theatrical entertainments, the control of narratives, and the author's place in this. Ideas of modernity are discussed and defined in terms of the production and consumption of popular print media, and Ainsworth's novels are demonstrated to be vital engagements with early Victorian popular culture. It is established that depictions of environments saturated with influential and uncontrollable literature in Jack Sheppard and Rookwood allow them to function as a satirical critique of both the critics and audience of Newgate narratives, and that one of Newgate's main concerns is the genre itself.